Measured Data Processing Method For Relative Motions Between Two Side-by-side Ships - Ping-an Shi; Jia-wei Ye (Institute of Advanced Engineering and Science, 2013)
In order to design and implement a wave compensation system to reduce the relative motion between two side-by-side ships in waves, a new method to process measured data of ship model test with contact measurement to study the characteristics of relative motion was presented. The reference co-ordinate systems and relative motions were defined, and the scheme of the model test was described. Then the Empirical Mode Decomposition(EMD) adaptive filter were designed, the frequency domain integration transform method based upon Fast Fourier Transform(FFT) were established. The procedure to transform acceleration signal into displacement was proposed and verified, and the processing results with and without EMD adaptive filter were compared. Finally, the relative motions consistent with reality were acquired, which indicates this method is effective for measured data processing. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1872